PENYALAHGUNAAN PERUNTUKAN RUANG TERBUKA HIJAU UNTUK BISNIS KULINER (STUDI KASUS DI PLUIT JAKARTA UTARA): The Misuse of Green Open Space Designation for Culinary Business (Case Study in Pluit North Jakarta) - Yapferonica; Setiawati, Anda (AMICUS CURIAE, 2024)
A debtor who is experiencing financial difficulties and cannot pay their loans or arrears is declared bankrupt by the Commercial Court. In the case of workers 'status bankruptcy, it is necessary to pay attention to whether the termination of the employment relationship can be carried out one-sidedly and whether the workers' wages, severance pay, and length of service compensation should all be taken into account and the cost of compensation rights due to the many discrepancies in the provisions of the bankruptcy law, PKPU, and labor law. The main question is how PT KIA Indonesia Motor is responsible for its employees to coincide with law No.  37 of 2004 on Insolvency and deferral of loan or delinquent payments, and how employees who are insolvent by the Act are legally protected. Normative legal research with secondary data is this type of research supported by preliminary evidence. Research is descriptive and reaches conclusions through deductive reasoning. The results showed that the separatist creditors are below the preferred creditors in the position of wage workers.